Analisis Pemanfaatan Serat Resam Sebagai Bahan Komposit Untuk Bahan Pembuatan Ujung Joran Pancing - Abdallah, Fajar; Rollastin, Boy; Harwadi, Harwadi (Politeknik Manufaktur Negeri Bangka Belitung, 2025)
Fishing has transformed from a traditional livelihood into an increasingly popular hobby among people, involving various age groups and locations. Fishing rods, as the main tool in the fishing process, function to catch fish by reducing the load and providing lifting power. This study aims to explore the use of resam fiber as an alternative material in making fishing rods, considering the limitations and high costs of graphite rods. The rod manufacturing process uses the Hand lay-up technique, where the resam fiber undergoes alkalization with 5% NaOH for 1, 2, and 3 hours, and variations in the number of fibers of 5, 10, and 15 strands. The results showed that specimens with 15 strands of fiber soaked for 2 hours produced the highest average tensile value of 44.6 MPa and the highest bending value of 57.6 MPa. This study shows the potential of resam fiber as a strong and affordable material for making fishing rods, providing a better alternative to graphite rods available on the market.